2021
DOI: 10.3892/ijmm.2021.5044
|View full text |Cite|
|
Sign up to set email alerts
|

KIF22 promotes bladder cancer progression by activating the expression of CDCA3

Abstract: Bladder cancer is a common malignant tumor of the urinary system and is associated with a high morbidity and mortality, due to the difficulty in the accurate diagnosis of patients with early-stage bladder cancer and the lack of effective treatments for patients with advanced bladder cancer. Thus, novel therapeutic targets are urgently required for this disease. Kinesin family member 22 (KIF22) is a kinesin-like DNA binding protein belonging to kinesin family, and is involved in the regulation of mitosis. KIF22… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
(49 reference statements)
0
4
0
Order By: Relevance
“…In BC, specific types of transcription factors can activate the expression of CDCA3, which then promotes the proliferation of BC cells, such as kinesin family member 22 (KIF22) and KIF4A. Similarly, research has shown that CDCA3 promotes cell cycle progression, accelerates cell growth, and promotes BC cell migration (11,18,19). Moreover, CDCA3 is a biomarker of chemosensitivity in NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…In BC, specific types of transcription factors can activate the expression of CDCA3, which then promotes the proliferation of BC cells, such as kinesin family member 22 (KIF22) and KIF4A. Similarly, research has shown that CDCA3 promotes cell cycle progression, accelerates cell growth, and promotes BC cell migration (11,18,19). Moreover, CDCA3 is a biomarker of chemosensitivity in NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…CDCA3 is another protein-coding gene. KIF22 promotes bladder cancer further development by activating CDCA3 [20]. CDCA4 is a protein-coding gene.…”
Section: Introductionmentioning
confidence: 99%
“…Bladder cancer (BLCA) is a common cancer with high morbidity and mortality rates worldwide. Most BLCA patients are often diagnosed in the late stages and lack effective treatments ( 1 , 2 ). There were about 81,400 new BLCA cases and 17,980 BLCA deaths in the United States in 2020 alone.…”
Section: Introductionmentioning
confidence: 99%